Influence Of Deep Image Learning Media Improving Students' Literacy Skills Class I Primary School - Samin, Mara; Brutu, Jihan Hijrahani Azizah; Hafizhah, Maryam; Harahap, Khairunnisa (Yayasan Pendidikan Islam Akmalia, 2023)
The research was motivated by the learning process of grade I teachers of SD Negeri 0206 Binanga, Barumun Tengah District, Padang Regency has not been able to use inretactive learning media optimally. The purpose of this study was to determine the influence of image learning media to improve the literacy of grade I students of SD Negeri 0206 Binanga, Barumun Tengah District, Padang Regency. The methods used in this study are observation and interview methods. The results showed that students' literacy skills tended to increase because the use of image learning media created a more meaningful and fun learning atmosphere, and increased student activity. So it can be concluded that image learning media affects the literacy ability of grade 1 students of SD Negeri 0206 Binanga. This means that this media learning method is quite effective in increasing student literacy.